Decellularized extracellular matrix (d-ECM): the key role of the inflammatory process in pre-regeneration after implantation. (10th January 2023) - Long, Jie; Qin, Zijin; Chen, Guo; Song, Baoqiang; Zhang, Ziang
Abstract : After d-ECM transplantation, residues in the d-ECM have different effects on immunological responses, leading to degradability, inflammation, and functional tissue remodeling. Abstract : Clinical medicine is encountering the challenge of repairing soft-tissue defects. Currently, natural and synthetic materials have been developed as natural scaffolds. Among them, the decellularized extracellular matrix (d-ECM) can achieve tissue remodeling following injury and, thus, replace defects due to its advantages of the extensiveness of the source and excellent biological and mechanical properties. However, by analyzing the existing decellularization techniques, we found that different preparation methods directly affect the residual components of the d-ECM, and further have different effects on inflammation and regeneration of soft tissues. Therefore, we analyzed the role of different residual components of the d-ECM after decellularization. Then, we explored the inflammatory process and immune cells in an attempt to understand the mechanisms and causes of tissue degeneration and regeneration after transplantation. In this paper, we summarize the current studies related to updated protocols for the preparation of the d-ECM, biogenic and exogenous residual substances, inflammation, and immune cells influencing the fate of the d-ECM.